EFEKTIVITAS DAN DAMPAK REVITALISASI PASAR TRADISIONAL TERHADAP JUMLAH KUNJUNGAN, PENDAPATAN PEDAGANG, DAN PENDAPATAN PASAR DI KOTA DENPASAR - Perwira Putra, I Kadek Dwi; Murjana Yasa, I Gusti Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; vol.6.No. 9. September 2017(pp.1628-1867), 2017)
The purpose study to determine the effectiveness and impact of revitalization of traditional markets on the number of visits, income traders, and market income in the city of Denpasar. This study was conducted on six using 92 samples. Data collection was done through interview, observation, and questionnaire. Data analysis technique used is difference test of two mean of paired samples, that is to know program effectiveness and Wilcoxon test statistic analysis, to know impact of revitalization of traditional market to visit number, merchant income, and market income. The result of data analysis shows that the level of effectiveness of traditional market revitalization is quite effective that is equal to 72,82 percent. Based on the result of statistical t test, revitalization of traditional market has positive and significant effect to the number of visits, merchant's income, and market income. Keywords : Traditional Market Revitalization, Number of Visits, Merchant's Revenues, Market Revenues